Schiff base and metal(II) complexes containing thiophene-3-carboxylate: Synthesis, characterization and antioxidant activities - Bingöl, M.; Turan, Nevin (Elsevier B.V., 2020)
A new Schiff base ligand (L) obtained from methyl 6-acetamide-2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylate and 2-hydroxy-3-methoxybenzaldehyde was synthesized. Then, the metal complexes of the Schiff base ligand were prepared with FeCl2·4H2O, CoCl2·6H2O, NiCl2·6H2O, [RuCl2(p-cymene)]2 and PdCl2(CH3CN)2 metal salts. Schiff base ligand and complexes were characterized using elemental analysis, 1H NMR, 13C NMR, FT-IR, LC-MS, UV–Vis., magnetic susceptibility, thermogravimetric analysis (TGA) methods. To determine the antioxidant activity of ligand and complex compounds, DPPH free radical removal activity, reduction force for ferric ions (Fe+3) to ferrous ions (Fe+2) according to the FRAP method, reducing force for cupric ions (Cu+2) to the cuprous ions (Cu+) with CUPRAC method and total antioxidant activities by ferric thiocyanate method were investigated. It was determined that Fe(II), Co(II), Ni(II) and Ru(II) complexes had octahedral structure and Pd(II) complex had a square planar structure. It was also determined that complex compounds generally showed more effective antioxidant activity than ligand. © 2019 Elsevier B.V.
Keywords: Antioxidant studies; Characterization; Metal(II) complexes; Schiff base